The Tetragonal Monoxide of Platinum: A New Platform for Investigating Nodal-Line and Nodal-Point Semimetallic Behavior - Li, Yang; Xia, Jihong; Srivastava, Vipul (Frontiers in Chemistry, 2020)
The search for new topological materials that are realistic to synthesize has attracted increasing attention. In this study, we systematically investigated the electronic, mechanical, and topological semimetallic properties, as well as the interesting surface states, of the tetragonal monoxide of platinum, which is realistic to synthesize, via a first-principles approach. Our calculated results indicate that PtO is a novel topological semimetal with double nodal lines in the kz = 0 plane and a pair of triple topological nodal points along the A’-M-A directions. Obvious surface states, including Fermi arc and drum-head-like surfaces, could be found around nodal points and nodal lines. The dynamic and mechanical stabilities of P42/mmc-type PtO were examined in detail via calculation of the phonon dispersion and determination of elastic constants, respectively. Some other mechanical properties, including the bulk modulus, Young’s modulus, shear modulus, Poisson’s ratio, and Pugh’s index, were considered in this study. P42/mmc-type PtO provides a good research platform for investigation of novel behaviors that combine mechanical properties and rich topological elements.